If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -1(7y + 10) = 7 + -1(9y + -6) Reorder the terms: 5y + -1(10 + 7y) = 7 + -1(9y + -6) 5y + (10 * -1 + 7y * -1) = 7 + -1(9y + -6) 5y + (-10 + -7y) = 7 + -1(9y + -6) Reorder the terms: -10 + 5y + -7y = 7 + -1(9y + -6) Combine like terms: 5y + -7y = -2y -10 + -2y = 7 + -1(9y + -6) Reorder the terms: -10 + -2y = 7 + -1(-6 + 9y) -10 + -2y = 7 + (-6 * -1 + 9y * -1) -10 + -2y = 7 + (6 + -9y) Combine like terms: 7 + 6 = 13 -10 + -2y = 13 + -9y Solving -10 + -2y = 13 + -9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '9y' to each side of the equation. -10 + -2y + 9y = 13 + -9y + 9y Combine like terms: -2y + 9y = 7y -10 + 7y = 13 + -9y + 9y Combine like terms: -9y + 9y = 0 -10 + 7y = 13 + 0 -10 + 7y = 13 Add '10' to each side of the equation. -10 + 10 + 7y = 13 + 10 Combine like terms: -10 + 10 = 0 0 + 7y = 13 + 10 7y = 13 + 10 Combine like terms: 13 + 10 = 23 7y = 23 Divide each side by '7'. y = 3.285714286 Simplifying y = 3.285714286
| 5=3x-50 | | a/5-2=7 | | 4*x-1=5 | | 5y+2y-16=3y+6-5 | | 17-20g=(13-5g)4 | | 40+15+0.25m=45+0.35m | | 12b+4+2= | | -5(-7x-10)=-39(5+7x) | | 9/8(m-57)=9/8(m-57) | | 1/5(d-200)=575 | | 3x+9=(x-2) | | (x^7/2)^3/7=8 | | (.10x+15)=(.15x+10) | | 16-15y=4 | | (2/3)g-4=(1/2)-2g | | 7-5(-6n-8)=14-3n | | -6(8x+1)=138 | | 5(y-4)/2=-4y | | f(x)=-3.25(-4.2)+22.41 | | 2/9t=8 | | 4(-3x+12)=6(8-2x) | | f(x)=-3.25x+22.41 | | 2y=x/2 | | 13.7b-6.5=-2.3b+83 | | -12*2/5 | | 10m+(0)=12 | | 6(x-4)=3x-24 | | 40.5p+14.40=4.50(p+3) | | 20+10x=4x-40 | | 10m+(-1)=12 | | y+34=-15 | | 6x-2=6x-54 |